Hope and a horizon of solidarity – An interview with Jeffrey C. Alexander: Interviewed by Anna Lund and Andrea Voyer (Sociologisk Forskning, 2020)
In this interview, Jeffrey C. Alexander describes the development of cultural sociology, the importance of collaborative work, and the inspiration he takes from his political action, and from the art and humanities. The interview focuses primarily on civil sphere theory (CST), and Alexander’s goal in moving towards Durkheimian and away from Parsonian conceptions of solidarity. Alexander addresses common misunderstandings and critiques of CST, describes the current project of the internationalization of CST, and applies the theory to the present crisis of a global pandemic and the social movement of Black Lives Matter. Finally, Alexander reflects upon life in the academic world and the importance of not only analyzing meaning as a cultural sociologist but also working with meaningful projects in order to not be alienated. Alexander was invited keynote speaker at the Sociologidagarna in March in Stockholm 2020, but due to the Corona pandemic the conference was cancelled. This interview took place through Zoom in three different locations (Stockholm, New Haven, and Coventry, Connecticut) on 22 June 2020.
Keywords: Jeffrey C. Alexander; cultural sociology; civil sphere theory; Meaning; Black Lives Matter; COVID-19